Study on flexural and demountable behavior of a modular light-gauge steel framed wall - Liu, Cong; Chen, Xin; Mao, Xiaoyong; He, Lin; Yuan, Jian (Journal of Civil Engineering and Management, 2023)
The demountable and modular light-gauge steel framed (DMLSF) wallboard is presented and used as non-load bearing exterior walls in medium and high-rise steel construction or temporary structure. Firstly, the bending tests were conducted on five wall modules to explore the flexural behavior of the wall. The numerical model was also established and verified by experimental results, and the simplified calculation method of the flexural capacity of the wall was proposed based on 68 numerical models. In addition, the reliability test of the seam between modules was finished to ensure the airtightness of the wall. Furthermore, the demountable behavior of the wall was studied by secondary loading tests and life cycle assessment (LCA) methodology. Results suggested that the wallboard could be used repeatedly after disassembled under the serviceability limit state. Raw materials, especially the insulation material, accounted for a large proportion of the environmental impact of the wallboard. The wallboard’s carbon dioxide emission and energy consumption could be significantly reduced when the wallboard was reused. This study can promote the application of the demountable concept in wall components and provide some guidance for the life cycle design of demountable structures.